2016
DOI: 10.3310/hsdr04260
|View full text |Cite
|
Sign up to set email alerts
|

Health Equity Indicators for the English NHS: a longitudinal whole-population study at the small-area level

Abstract: Background: Inequalities in health-care access and outcomes raise concerns about quality of care and justice, and the NHS has a statutory duty to consider reducing them. Objectives: The objectives were to (1) develop indicators of socioeconomic inequality in health-care access and outcomes at different stages of the patient pathway; (2) develop methods for monitoring local NHS equity performance in tackling socioeconomic health-care inequalities; (3) track the evolution of socioeconomic health-care inequalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 151 publications
0
34
0
Order By: Relevance
“…Access to health care services is often one of the indicators of equity in health care provision [10]. Providing health care on equal terms has become a challenge for the health care system all over the world [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Access to health care services is often one of the indicators of equity in health care provision [10]. Providing health care on equal terms has become a challenge for the health care system all over the world [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In this scoping review, we identified and reviewed studies 35 which used a quantitative methodology to investigate intra-national (in-country) 36 variations in access across the care pathway and health systems of different 37 inequality groups among populations of adult MS patients. the Cochrane and Campbell Equity methods group checklist [23] to guide the development of the study protocol, study implementation and presentation of 1 findings. This study was funded by Salford Royal NHS Hospitals Foundation Trust.…”
mentioning
confidence: 99%
“…As the focus was on adult MS patients, we excluded any study in which 37 more than 5% of the population was under 16 years of age. We also excluded 38 studies comparing MS patients with the general population or with other patient 39 groups, studies investigating uptake of alternative or complementary therapies, those 40 that focused on uptake of lifestyles rather than the services which promote lifestyle 41 5 modification, those investigating DMT adherence rather than prescription and studies 1 where the outcome was perceived or reported need, rather than comparative need. The full characteristics of the 36 studies is shown in supplementary The effect of gender was examined across all access subcategories for which there 20 were studies, and disability and socioeconomic status across all but one.…”
mentioning
confidence: 99%
“…Less well known, however, is the greater increase in emergency admission of patients for inpatient hospital treatment (Blunt, 2013 …”
Section: The Rise and Rise Of Emergency Admissionsmentioning
confidence: 99%
“…his requires better integration of local patient information between primary, secondary and social care, with speciic attention to deprivation. NHS England has now started producing local indicators of inequality in potentially avoidable emergency hospitalization that could be used routinely to ind out whether local initiatives are making a diference to local health inequalities (Cookson et al, 2016a). hese indicators show how well each local NHS area is doing at tackling inequality in avoidable admissions compared with other similar NHS areas.…”
Section: Coordinated Carementioning
confidence: 99%